The value of FT4/TSH ratio in the differential diagnosis of Graves’ disease and subacute thyroiditis - Zhang, Yingjie; Wang, Yu; Liu, Miao; Wei, Lingge; Huang, Jianmin; Dong, Ziqian; Guan, Meichao; Wu, Weijie; Gao, Jianqing; Huang, Xiaojie; Guo, Xin; Xie, Peng (Frontiers in Endocrinology, 2023)
Objective: To explore the value of the FT4/TSH ratio in the etiological diagnosis of newly diagnosed patients with thyrotoxicosis. Methods: The retrospective study was conducted on 287 patients with thyrotoxicosis (122 patients with subacute thyroiditis and 165 patients with Graves' disease) and 415 healthy people on their first visit to our hospital. All patients underwent thyroid function tests including the measurement of T3, T4, FT3, FT4, and TSH. The receiver operating characteristic (ROC) curve was employed to evaluate the value of FT4/TSH in the differential diagnosis of Graves' disease and subacute thyroiditis, and compared with other related indicators. Results: The area under the curve of FT4/TSH for diagnosing Graves' disease and thyroiditis was 0.846, which was significantly larger than the area under the curve of T3/T4 ratio (P< 0.05) and FT3/FT4 ratio (P< 0.05). When the cut-off value of the FT4/TSH ratio was 5731.286 pmol/mIU, the sensitivity was 71.52%, the specificity was 90.16%, the positive predictive value was 90.77% and the negative predictive value was 70.06%. The diagnostic accuracy was 79.44%. Conclusion: FT4/TSH ratio can be used as a new reference index for the differential diagnosis of thyrotoxicosis.